Design of Monitoring and Separating Dustbin System using Internet of Things - Rizal Mujaddid Irsyad; Luqman Hadi Dwi Satryo; Annisa Larasati Febrianingrum; Feri Adriyanto (Journal of Electrical, Electronic, Information, and Communication Technology, 2020)
The growing population is causing a big problem in terms of waste.  Garbage sorting efforts need to be made, especially the separation between organic and non-organic garbage, so that non-organic garbage that can still be recycled is not contaminated by organic garbage containing water and oil. Moreover, it requires swift handling of trash bins that are full so that trash does not accumulate and become an epidemic. For that we need innovation in the form of technology that is able to overcome these problems. This paper is designed IoT-based garbage for monitoring and separating dustbin. The design of garbage was made using Arduino UNO as a microcontroller that can monitor and sort garbage automatically. There are 2 stages in the garbage sorting process. The first stage is the metal and non-metal separation, and then the second stage is the organic and non-organic stages. When the trash is full, the trash can lid will be locked and then the system will send a notification to the garbage manager regarding the location/position of the trash and the weight of the trash. This research method includes 4 stages such as analysis of needs and working methods, design of hardware and software design, implementation, and finally testing of the design.Keywords— garbage, waste management, garbage sorting, separting dustbin, internet of things